Optimal asset allocation for participating contracts with mortality risk under minimum guarantee. Issue 14 (17th July 2020) - Wu, Sang; Dong, Yinghui; Lv, Wenxin; Wang, Guojing
Abstract: We investigate an optimal investment problem of participating insurance contracts with mortality risk under minimum guarantee. The insurer aims to maximize the expected utility of the terminal payoff. Due to its piecewise payoff structure, this optimization problem is a non-concave utility maximization problem. We adopt a concavification technique and a Lagrange dual method to solve the problem and derive the representations of the optimal wealth process and trading strategies. We also carry out some numerical analysis to show how the portfolio insurance constraint impacts the optimal terminal wealth.